Independent Recruitment of Duplicated β-Subunit-Coding NAD-ME Genes Aided the Evolution of C4 Photosynthesis in Cleomaceae - Tronconi, Marcos A.; Hüdig, Meike; Schranz, M. Eric; Maurino, Veronica G. (Frontiers in Plant Science, 2020)
In different lineages of C4-plants, the release of CO2 by decarboxylation of a C4 acid near rubisco is catalyzed by NADP-malic enzyme (ME) or NAD-ME, and the facultative use of phosphoenolpyruvate carboxykinase. The co-option of gene lineages during the evolution of C4-NADP-ME has been thoroughly investigated, whereas that of C4-NAD-ME has received less attention. In this work, we aimed at elucidating the mechanism of recruitment of NAD-ME for its function in the C4 pathway by focusing on the eudicot family Cleomaceae. We identified a duplication of NAD-ME in vascular plants that generated the two paralogous lineages: α- and β-NAD-ME. Both gene lineages were retained across seed plants, and their fixation was likely driven by a degenerative process of sub-functionalization, which resulted in a NAD-ME operating primarily as a heteromer of α- and β-subunits. We found most angiosperm genomes maintain a 1:1 β-NAD-ME / α-NAD-ME (β/α) relative gene dosage, but with some notable exceptions mainly due to additional duplications of β-NAD-ME subunits. For example, a significantly high proportion of species with C4-NAD-ME-type photosynthesis have a non-1:1 ratio of β/α. In the Brassicales, we found C4 species with a 2:1 ratio due to a β-NAD-ME duplication (β1 and β2); this was also observed in the C3 Tarenaya hassleriana and Brassica crops. In independently evolved C4 species, all three genes were affected by C4 evolution with α- and β1-NAD-ME driven by adaptive selection. In particular, the β1-NAD-MEs possess many differentially substituted amino acids compared with other species and the β2-NAD-MEs of the same species. Five of these amino acids are identically substituted in β1-NAD-ME of G. gynandra and C. angustifolia, two of them were identified as positively selected. Using synteny analysis, we established that β-NAD-ME duplications were derived from ancient polyploidy events and that α-NAD-ME is in a unique syntenic context in both Cleomaceae and Brassicaceae. We propose that gene duplications provided the basis for the recruitment of NAD-ME in Cleomaceae and that all members of the NAD-ME gene family have been adapted to fit the C4-biochemistry. Also, the extra β-NAD-ME gene copy was independently co-opted for the exclusive function in the C4-pathway.